X̄ chart with variable sample size and sampling intervals - Costa, Antonio F. B. [UNESP] (My University, 1997)
Recent theoretical studies have shown that the X̄ chart with variable sampling intervals (VSI) and the X̄ chart with variable sample size (VSS) are quicker than the traditional X̄ chart in detecting shifts in the process. This article considers the X̄ chart with variable sample size and sampling intervals (VSSI). It is assumed that the amount of time the process remains in control has exponential distribution. The properties of the VSSI X̄ chart are obtained using Markov chains. The VSSI X̄ chart is even quicker than the VSI or VSS X̄ charts in detecting moderate shifts in the process.
Keywords: Average Time to Signal; Control Charts; Statistical Process Control; Variable Sample Size Control Charts; Variable Sampling Interval Control Charts; Markov processes; Statistical methods; Variable sample size (VSS); Variable sampling intervals (VSI); Process control